Skrining Kesehatan Lanjut Usia Melalui Program Edukasic USK - Ardia Putra; Nurhasanah Nurhasanah; Nurul Hadi (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
This community service activity is planned to be held in Cot Preh Village, Kuta Baroe District, Aceh Besar. This gampong (village) is one of the gampongs located in the working area of the Lambaro Health Center, which has access to and good reception of health information. In addition, health cadres, village heads, and Cot Preh village officials fully support the health education programs provided by the community service team. This service activity is one of the preventive and promotive actions of several community health empowerment service efforts. The health empowerment activities focus on the elderly group regarding the "elderly health screening" program to provide health services to the elderly in Gampong Cot Preh. The community service team's activities include health screening (blood pressure, blood sugar, TB, and weight), followed by filling in MNA and Mini-Cog data. The purpose and outcome of this community service are to improve the health of the elderly in Gampong Cot Preh. Then, increasing public understanding of the importance of health screening for the elderly, raising elderly awareness of the importance of maintaining health, increasing knowledge and the role of families and community health center cadres in supervising the health of the elderly and achieving a healthy, independent and prosperous quality of life.